Review of Recent Research on the Potential of Cellulose NanoCrystals (CNCs) in Improving Heat Transfer Processes - Aqeel A.A.K.A.; Hajjaj S.S.H.; Mohamed H.; Gomaa M.R.; Obeidat F.S. (Springer Science and Business Media Deutschland GmbH, 2025)
Cellulose NanoCrystals (CNCs) are materials created by acid degradation of wood fiber, giving them unique qualities, such as low cost, excellent stability, large surface area, advantageous mechanical properties, renewability, and low toxicity. These features make CNCs ideal for the performance of cooling fluids and nanocomposites in thermal cooling systems. This article thoroughly analyzes several studies on CNCs, focusing on four primary areas: their mechanical characteristics, impact on thermal and tribological properties, performance enhancement, and their role in improving heat transfer in radiator coolants. Each section presents relevant studies and key findings. The review provides insights into CNC's mechanical properties, thermal conductivity, viscosity, tribological characteristics, and impact on fluid performance and heat transfer efficiency. According to the findings of earlier studies, CNCs machines have a high tensile strength estimated at 7.5?7.7 GPa and an elastic modulus of 140 GPa. CNC-based nanofluids improve cooling performance by four times viscosity and 11?20% thermal transfer when combined with other nanomaterials. This is great for the efficiency of the thermal system. Utilizing CNCs-based nanofluids is promising because they increase efficiency in solar energy collectors by about 5.8%, reduce wear rate in machinery lubricants by up to 69% compared to base oil, and improve engine operation efficiency in cooling automobile motors by an average of 0.69% when 0.5% of nanocellulose is added to the radiator coolant. CNCs provide a practical and eco-friendly way to improve transportation. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.